2018
DOI: 10.1111/1759-7714.12766
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for disseminated intravascular coagulation in patients with lung cancer

Abstract: BackgroundThe mortality rate from disseminated intravascular coagulation (DIC) is higher in patients with lung cancer than in non‐lung cancer patients. Moreover, the prevalence of DIC varies among the pathologic types of lung cancer. This study analyzed the relationship between coagulation factors and the pathologic types of lung cancer.MethodsTwenty‐six patients with progressive, inoperable stage IIB or higher lung cancer (20 men, 6 women; mean age 71 years; 11 Adeno, 10 squamous cell carcinoma, and 5 small c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Study conducted by Nakano et al altered levels of blood coagulation factors in different pathologic types of lung cancer. 21 In addition fibrin/fibrinogen degradation products, fibrinogen, and D-dimer levels differed significantly between cancer patients and the control group. These findings are consistent with our study which also showed raised level of D-dimer and PT in different histopathologic types of squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 90%
“…Study conducted by Nakano et al altered levels of blood coagulation factors in different pathologic types of lung cancer. 21 In addition fibrin/fibrinogen degradation products, fibrinogen, and D-dimer levels differed significantly between cancer patients and the control group. These findings are consistent with our study which also showed raised level of D-dimer and PT in different histopathologic types of squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 90%
“…Evidence suggests that the coagulation-fibrinolysis system is closely related to the progression of LC and that activation of coagulation is common in LC 15 , 16 . A previous prospective study demonstrated that LC patients had higher blood coagulation parameters than healthy volunteers, including PLTs, FIB, thrombomodulin, and D-dimer 17 . A retrospective study in Poland found that the frequency of thrombocytosis in surgically treated patients with non-small cell lung cancer (NSCLC) was 10.2% 18 .…”
Section: Discussionmentioning
confidence: 95%
“…The expression of coagulation factors may vary with the pathological type of lung cancer, and the level of anti-thrombin in patients with SCC is significantly lower than that in adenocarcinoma patients. [24] Tas et al have found that D-dimer levels in patients with SCC are higher than those in other pathological types. [23] Li and other studies have also shown that SCC has significantly higher Fbg levels than adenocarcinoma, and Fbg and platelet count levels are higher in stage III and IV than in stage I-II.…”
Section: Discussionmentioning
confidence: 99%
“…NSE is a type of tumor markers of SCLC, [31] and related studies have shown that plasma Fbg often increases obviously in SCLC patients. [7,24] The mechanisms activating coagulation and fibrinolysis in SCLC patients and NSCLC patients are different. In SCLC, tumor cells can release tissue factor to activate coagulation system directly, whereas in NSCLC, host macrophages release factors that activate the fibrinolytic system.…”
Section: Discussionmentioning
confidence: 99%